Control of Aspergillus postharvest rot on plum tomato by potassium metabisulfite and potassium sorbate - Nanasombat, Suree; Phunpruch, Saranya (Asia-Pacific Journal of Science and Technology, 2025)
In this study, fungal contamination of plum tomato fruits (Solanum lycopersicum) was preliminarily examined by the dilution plating method. The tomato samples were highly contaminated by molds and yeasts (1.0x105 - 1.4x108 CFU/g), including Aspergillus, Geotrichum, Penicillium, Rhizopus, Candida, Cryptococcus and Rhodotorula. The mold strains that contaminated the tomatoes to the greatest extent were Penicillium and Rhizopus. Three fungal isolates (Aspergillus niger T6D5, Candida guilliermondii T7D4 and Rhodotorula mucilaginosa T7D5) were selected for further in vitro study. Then, the antifungal activity of organic acids (citric and tartaric acids) and salts (potassium acetate, potassium metabisulfite and potassium sorbate) against molds and yeasts was investigated. Salt solutions showed higher inhibitory effects than did acid solutions. Interestingly, A. niger T6D5 showed the highest susceptibility to potassium sorbate and potassium metabisulfite at 0.01-1% (w/v) MIC, respectively, compared to other fungi. In yeasts, potassium metabisulfite effectively inhibited the growth of C. guilliermondii T7D4 and R. mucilaginosa T7D5 at 0.25% (w/v) MIC. The use of organic acids and salts to control the growth of A. niger T6D5 on tomatoes was investigated. Among all the salts and acids tested, 1% (w/v) potassium metabisulfite and 3% (w/v) potassium sorbate completely inhibited the growth of A. niger T6D5 on tomatoes.